OPTIMIZING HYDROGEN PRODUCTION FROM THE PHOTOVOLTAIC-POWERED ALKALINE WATER ELECTROLYZER - Pramujo Widiatmoko; Hary Devianto; Habibil Ghifary; Fran Felix Nurdiansyah; J.F. Simorangkir (Balai Besar Bahan dan Barang Teknik, 2021)
Energy transition has arisen its attention towards hydrogen technology. Green hydrogen can be produced from renewable energy sources such as photovoltaic (PV) through water electrolysis. However, its efficiency needs to be improved due to the intermittent nature of the remote microgrids. This study focuses on the design of SEPIC DC/DC converter and alkaline water electrolytic cells configuration on a 175 Wp polycrystalline silicon PV module. A homemade alkaline water electrolyzer of 3 M KOH was used and modeled numerically on Simulink MATLAB software. The converter and electrolytic cells configuration were designed for 1000, 800, 600 and 400 W/m2 solar irradiances. The results indicate that the required inductor decreased from 2.2 mH to 1.1 mH while the required capacitor increased from 10 mF to 27 mF as the solar irradiance increased. In a dynamic condition, the converter efficiency reached a maximum of 94.35%. Further, hydrogen production achieves 4.81 to 5.93 kg-H2/year as the installed electrolytic cell’s capacity increased from 70.2 to 174.9 W. The Levelized Cost of Hydrogen under unlimited photovoltaic power capacity is 13.08 USD/ kg-H2